The Stay in the WHOA: Right on Target or Missing the EU Mark? A comparison of stay provisions between the ‘Wet homologatie onderhands akkoord ter voorkoming van faillissement’ and the EU Proposal for a Directive on preventive restructuring frameworks - Lorjé, Trieneke (Student Undergraduate Research E-journal!, 2019)
This paper compares the stay provisions of The Proposal for a Directive of the European Parliament and of the Council on preventive restructuring frameworks (hereafter: EU Proposal) and the “Wet homologatie onderhands akkoord ter voorkoming van faillissement” (WHOA) by asking: How does Article 375 WHOA compare to Article 6 EU Proposal? When compared, the texts mentioned above, reveal that the main issue is the length of the stay period in the WHOA. While technically being in line with the EU Proposal, the stay period in the WHOA is on the shorter side of the minimum standard which could frustrate the convergence of EU and national restructuring laws.